2021
DOI: 10.1093/bjs/znab383
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy using low-dose versus standard radiation dose CT in suspected acute appendicitis: prospective cohort study

Abstract: Background Contrast-enhanced CT is the reference standard used in diagnostic imaging for acute appendicitis in adults. The radiation dose has been of concern. This study aimed to assess whether a lower radiation dose would affect the diagnostic accuracy of CT. Methods This was a prospective single-centre cohort study of patients (aged over 16 years) with suspected appendicitis evaluated for enrolment in concurrent APPAC II–II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…Despite the exposure of patients to ionizing radiation, the use of a CT as first-line imaging for evaluating acute abdominal pain has been advocated before, given its higher accuracy compared to US [ 29 ]. Moreover, Haijanen et al reported the use of low dose ionizing radiation in CT as still accurate in identifying an acute appendicitis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the exposure of patients to ionizing radiation, the use of a CT as first-line imaging for evaluating acute abdominal pain has been advocated before, given its higher accuracy compared to US [ 29 ]. Moreover, Haijanen et al reported the use of low dose ionizing radiation in CT as still accurate in identifying an acute appendicitis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo publicado na British Journal of Surgery em 2021 destaca que a TC de baixa dose é quase tão precisa quanto a TC de dose padrão na identificação de apendicite aguda, mas com uma exposição significativamente menor à radiação. Este estudo apoia a implementação ativa de modalidades de baixa dose na prática clínica para minimizar a exposição à radiação, mantendo a precisão diagnóstica e ajudando a reduzir as apendicectomias negativas(Haijanen et al , 2021). Além disso, artigo da BMC Gastroenterology de 2023 discute um novo escore de apendicite adulta que melhora a precisão diagnóstica.…”
unclassified